2023
DOI: 10.1007/s13555-023-01002-1
|View full text |Cite
|
Sign up to set email alerts
|

Spesolimab Efficacy and Safety in Patients with Moderate-to-Severe Palmoplantar Pustulosis: A Multicentre, Double-Blind, Randomised, Placebo-Controlled, Phase IIb, Dose-Finding Study

A. David Burden,
Robert Bissonnette,
Alexander A. Navarini
et al.

Abstract: Introduction We evaluated the anti-interleukin-36 receptor antibody spesolimab in patients with moderate-to-severe palmoplantar pustulosis (PPP). Methods This phase IIb trial comprised a loading dose period to week (W) 4, then maintenance dosing to W52. Patients were randomised 2:1:1:1:2 to subcutaneous spesolimab 3000 mg to W4 then 600 mg every 4 weeks (q4w), spesolimab 3000 mg to W4 then 300 mg q4w, spesolimab 1500 mg to W4 then 600 mg q4w, spesolimab 1500 mg to W4, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In addition, efficacy variations in ethnicity and severity of disease were observed in the clinical studies described above 9,10 . It is an interesting point that the efficacy was more pronounced in non‐Asian patients.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, efficacy variations in ethnicity and severity of disease were observed in the clinical studies described above 9,10 . It is an interesting point that the efficacy was more pronounced in non‐Asian patients.…”
mentioning
confidence: 85%
“…Spesolimab is a humanized anti‐interleukin‐36 receptor monoclonal antibody, showing a great lesion clearance incidence in patients with generalized pustular psoriasis (GPP) 8 . However, neither of the two published clinical trials of spesolimab for PPP met the primary efficacy endpoint, which indicated its modest benefits in palmoplantar pustulosis 9,10 . Although GPP and PPP are considered two major subtypes of pustular psoriasis, they have many differences.…”
mentioning
confidence: 99%
“…We thank Dr Hu and colleagues for their Letter to the Editor regarding our Phase IIb study of spesolimab in palmoplantar pustulosis (PPP) [ 1 ], and we welcome this opportunity to discuss the important points raised. The refractory nature of PPP means that there are limited treatment options for patients [ 2 ], and any factors potentially influencing treatment response should be explored to enable future clinical trial planning.…”
mentioning
confidence: 99%
“… First, Hu et al ask whether the sometimes self-limiting nature of PPP could help to explain the lack of significant difference in the primary endpoint of our study. We consider this a possibility and have acknowledged the fact that variations in PPP disease severity over time could have masked a treatment effect of spesolimab during the trial [ 1 ]. As Hu et al mention, demonstrating a significant difference between a trial drug and placebo in PPP trials is indeed challenging because of the disease course.…”
mentioning
confidence: 99%
See 1 more Smart Citation